Expanding the Phenotype of Congenital Glucocorticoid Deficiency: An Iranian Patient with Cholestasis due to Pathogenic Variants in the MC2R Gene - Shohreh Maleknejad; Setila Dalili; Ameneh Sharifi; Afagh Hassanzadeh Rad; Reza Bayat; Bahareh Rabbani; Nejat Mahdieh (International Journal of Endocrinology)
Familial glucocorticoid deficiency is caused by variants in the MC2R and MRAP genes. We report an Iranian patient with congenital glucocorticoid deficiency and cholestasis due to pathogenic variants in the MC2R gene. This is the first documented case of a patient with conditions. Clinical evaluations and lab assessments were conducted on a six-month-old male infant. Next-generation sequencing identified the genetic causes of the disease, and Sanger sequencing confirmed the variants through segregation analysis. The clinical presentation included prolonged jaundice, progressive skin hyperpigmentation, seizures, fever, and a large umbilical hernia. Two variants in the MC2R gene, c.560delT and c.676G > C, were detected and classified as pathogenic and likely pathogenic, respectively. The cooccurrence of cholestasis and glucocorticoid deficiency illustrates the clinical heterogeneity caused by MC2R variants. The prevalence of c.560delT and c.676G > C between Iranian populations suggests these variants may be common. The high frequency of c.560delT could be attributed to a founder effect.